1997
DOI: 10.1007/bf01349993
|View full text |Cite
|
Sign up to set email alerts
|

Critical appraisal of surgical venous access in children

Abstract: Central venous catheters (CVC) have become an important adjunct to the overall management of paediatric patients, but their use is associated with frequent complications resulting in premature removal. This report evaluates the insertion techniques and complications of 295 consecutive surgically inserted CVC from 1987 to 1991 in a paediatric hospital. Fully implanted catheters had significantly less incidence of catheter-related problems necessitating removal (infection, dislodgment, leaking, blockage, or migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
11
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 19 publications
4
11
0
Order By: Relevance
“…Our study confirms previous reports [2] demonstrating that TID survival was better than TL, with accidental removals and infection rates accounting for most differences. Our rates of infection and accidental removal compare favorably with those reported in the literature [2].…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…Our study confirms previous reports [2] demonstrating that TID survival was better than TL, with accidental removals and infection rates accounting for most differences. Our rates of infection and accidental removal compare favorably with those reported in the literature [2].…”
Section: Discussionsupporting
confidence: 95%
“…The single most important modifiable variable contributing to catheter survival was catheter tip location in the SVC/right atrial junction. This finding supports the reports of others [2,5].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Since we only include patients with removed ports, patients in our study were older (>9 year of age) than other patients reported in previous studies, however, demographic features of patients did not show significant difference in CTG and CG. These findings are similar to that of previous studies 22,23 .…”
Section: Discussionsupporting
confidence: 93%
“…These tunneled catheters allow for frequent blood sampling and administration of medication and nutrition in pediatric patients without the discomfort and anxiety of frequent needle sticks. The use and benefits of long-term central venous access devices (CVADs) in children are well established (1)(2)(3)(4)(5).…”
mentioning
confidence: 99%